KOMPOSISI DAN EFISIENSI PENGENDALIAN GULMA PADA PERTANAMAN KEDELAI DENGAN PENGGUNAAN BOKASHI - Hidayati Mas'ud (Universitas Tadulako, 2009)
The research aimed at studying the effective way of weeds control and the usage of organic fertilizer in soy cultivation at dry land. The research conducted was from July to September 2007, located in the Laboratory and Experimental Farm of Agriculture Department in Tadulako University, Palu. The research used a Randomized Block Design with a two Factorial Experiment. The first factor was four different kinds of weeds control (P): without weeds control (p0), manual control using mowing (p1), culture control technique using mulch (p2), and chemical control using oxyfluorofen (p3). The second factor was three levels of bokashi fertilizers (B): without bokashi (b0), 10 ton ha-1 bokashi (b1), and 20 ton ha-1 (b2). The results of vegetation analysis 10 weeks after planting showed that 21 kinds of weeds were found consisting of 14 kinds of broad leave classes, 6 kinds of grass classes (graminae) and only a kind of sedges class (cyperaceae). The results indicated that the efficiency of the control treatment in controlling weeds was significantly lower than other treatments. The chemical treatment in controlling weeds had similar effect and efficiency as the mulch treatment. However, the use of mulch has more advantages due to its cost and time efficiencies and environmentally friendly when applied in crop cultivation.